Survival after abdominoperineal and sphincter-preserving resection in nonmetastatic rectal cancer: a population-based time-trend and propensity score-matched SEER analysis - Warschkow, René; Marti, Lukas (Gastroenterology research and practice, 2017)
Background. Abdominoperineal resection (APR) has been associated with impaired survival in nonmetastatic rectal cancer patients. It is unclear whether this adverse outcome is due to the surgical procedure itself or is a consequence of tumor-related characteristics. Study Design. Patients were identified from the Surveillance, Epidemiology, and End Results database. The impact of APR compared to coloanal anastomosis (CAA) on survival was assessed by Cox regression and propensity-score matching. Results. In 36,488 patients with rectal cancer resection, the APR rate declined from 31.8% in 1998 to 19.2% in 2011, with a significant trend change in 2004 at 21.6% (). To minimize a potential time-trend bias, survival analysis was limited to patients diagnosed after 2004. APR was associated with an increased risk of cancer-specific mortality after unadjusted analysis (HR = 1.61, 95% CI: 1.28-2.03, ) and multivariable adjustment (HR = 1.39, 95% CI: 1.10-1.76, ). After optimal adjustment of highly biased patient characteristics by propensity-score matching, APR was not identified as a risk factor for cancer-specific mortality (HR = 0.85, 95% CI: 0.56-1.29, ). Conclusions. The current propensity score-adjusted analysis provides evidence that worse oncological outcomes in patients undergoing APR compared to CAA are caused by different patient characteristics and not by the surgical procedure itself.